2008
DOI: 10.1002/ptr.2318
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic effects of coconut (Cocos nucifera) extract in rats

Abstract: A warm water crude extract of coconut milk and a coconut water dispersion were investigated for their antiulcerogenic effects in male Wistar albino rats. Ulcers were induced in the male rats by subcutaneous administration of indomethacin (40 mg/kg) using standard procedures. The ulcer inhibition rate (UIR) was taken as a measure of the cytoprotection offered by test substances. Coconut milk (2 mL daily oral feeding) produced a stronger percentage (54%) reduction in the mean ulcer area than coconut water (39%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 5 publications
1
24
0
1
Order By: Relevance
“…It is an old practice to use fungicides as defense against skin diseases, including mycotic transmission, in many parts of the world [7]. Coconut water and milk are also used as an antiulcer treatment and food supplement due to its high nutritional value [8]. At present, the use of agricultural waste is receiving more attention than in the past for the production of natural products because these are cheaper, highly effective and the best solution for the disposal of waste.…”
Section: Introductionmentioning
confidence: 99%
“…It is an old practice to use fungicides as defense against skin diseases, including mycotic transmission, in many parts of the world [7]. Coconut water and milk are also used as an antiulcer treatment and food supplement due to its high nutritional value [8]. At present, the use of agricultural waste is receiving more attention than in the past for the production of natural products because these are cheaper, highly effective and the best solution for the disposal of waste.…”
Section: Introductionmentioning
confidence: 99%
“…The other 400 or so formulations are still under close scrutiny. In the case of coconut milk, as reported in [4,8] and also in several other publications, it would appear that this beverage is endowed with important positive effects on human health. Any entrepreneurs or small start-up companies interested in preparing a nutraceutic formulation from coconut milk would now have a good starting point in this long list of proteins to enucleate some having unique properties on human well-being.…”
Section: Discussionmentioning
confidence: 76%
“…The main saturated fat that it contains, lauric acid, is also found in mother's milk and has been shown to promote brain development and bone health [3]. Among other health effects, coconut milk has been reported to have hyperlipidemic balancing qualities as well as antimicrobial properties in the gastrointestinal tract and healing properties in mouth ulcers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Later, a study was conducted on male Wistar albino rats to investigate the effect of coconut extracts on ulcer. The result showed that CM displayed better antiulcerogenic effects than CW, even similar effects of sucralfate [14]. However, it is not known the active compound contained in CM that imposed such effect.…”
Section: Introductionmentioning
confidence: 95%